Assessing Socioeconomic Risks of Climate Change on Tenant Farmers in Pakistan - Yousafzai, Muhammad Tariq; Shah, Tariq; Khan, Salim; Ullah, Sana; Nawaz, Muhammad; Han, Heesup; Ariza-Montes, Antonio; Molina-Sánchez, Horacio; Vega-Muñoz, Alejandro (Frontiers in Psychology, 2022)
The study uses a transformative worldview to give voice to an economically marginalized group of tenant farmers vulnerable to climate changes due to their calamity prone geographical location. Drawing on anthropogenic global warming (AGW) theory lens, we examine the impact of manmade actions on climate change in District “Swat” and “Malakand” of Khyber Pakhtunkhwa (KPK) province, Pakistan using a sequential mixed methods research design. Through this research design, the results of quantitative survey were complemented with a qualitative analysis of in-depth interviews. In first phase, we conducted a survey of 200 tenant farmers, followed by second wave of data collection involving 12 open-ended in-depth interviews (IDIs). The both qualitative and quantitative results suggest that farmers in both districts are affected by climate change although their crop yield had progressively increased signaling better coping and survival skills than other parts of country. Majority of respondents believed that climate change is something beyond their control in disagreement with AGW theory. Major economic losses were specifically, due to sudden alterations in weather patterns, such as floods, and hailstorms that reduce productivity as well as results in food waste with no avenues available to reclaim the energy laden in organic food waste. Besides, a productivity loss was attributed to outdated farming, lack of awareness regarding sharecropping and crop loan insurance practices. The study concludes that farmers are most vulnerable to climate change in socioeconomic terms as such changes impact their income sources; This inwardly compels cash strapped tenant farmers to delve in practice of informal credit with substantive risks attached which further deteriorates their livelihoods. The study offers understanding of how low-literate and economically marginalized indigenous tenant farmers cope to climate change and offers policy recommendations to advocate for the rights to earn sustainable livelihoods in the face of grand climate challenge.